Move Up, Live Up: Dance Activities as a Way of Motivating Students Participating in Progressive Limited Face-to-face Classes - Recede, Reynald Alfred A.; Bulay-og, Leah Sablayan; Reyes, Joyce E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Dancing is a popular form of physical exercise. Researches have shown that dancing can increase self-esteem and improve our mind and body to become more productive. The aim of this study is to explore the impact of "Galaw Pilipinas" calisthenics exercise on the motivation of students as they go back to face-to-face classes. The sample for this study is composed of 16 female and 15 male Senior High School students of a public national high school in Marikina City. Senior High School students' pretest results; mean score was 87.52, the standard deviation was 4.67 and the standard error mean was 0.84. While the Senior High School students' posttest results; mean score was 95.87, the standard deviation was 3.24 and the standard error mean was 1.96. A paired samples t-test was conducted to evaluate the impact of the Galaw ng Pilipinas dance routine on student motivation. The results showed a significant increase in the marks of the students’ pretest (M = 87.52, SD =4.67 to posttest (M = 95.87, SD = 3.24), t = 9.1399, n = 31, p= .0001 which is less than 0.05 (two-tailed). By conventional criteria, this difference is considered to be statistically significant. Hence, the dance routine greatly affects the increase in motivation of the students.